The Poetics of Writing the Self: Pierre Sentat’s Verse - Mark, Vera (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
Analysis of the French and Gascon verse composed by a cobbler-poet from southwestem France reveals how local poetry is concerned with representations of the personal, the historical, and the political. The cobbler in question served a prison sentence after being accused of collaborationism during World War II. As a result, in his old age he wrote poetry, in which he presented positive narrative selves — his and others — in order to reintegrate himself into local society. The approach taken combines formal analysis of the rhetorical device of capitalization in selected verses in conjunction with larger psycho-social meanings, as keys to understanding representation of self.